Reading to Be: The role of academic reading in emergent academic and professional student identities - Maguire, Moira; Reynolds, Ann Everitt; Delahunt, Brid (Journal of University Teaching and Learning Practice, 2020)
Despite the widespread acknowledgement of the importance of academic reading, much research tends to focus on academic writing. The role of academic writing in the development of academic and professional identities is generally accepted. In contrast, the role of academic reading has been less visible in the literature, and when discussed, it tends to be conceptualised as a generic skill.In this paper, we explore the role of reading in emergent academic identities in undergraduates. We reflect on research with our own Nursing and Midwifery students that highlighted the role of reading in the development of ‘writing capital.’ Drawing on this and wider evidence we explore how, through academic reading, students begin to recognise, and then participate in the scholarly conversations that construct knowledge within disciplines. We argue that academic reading, like academic writing, is a complex ongoing process that involves multiple transitions, rather than a skill that can, and should, be mastered early on. We contend that educators need to consider how and where academic reading is addressed within academic programmes. Moreover, we suggest ways to make room for it within our curricula and engage students in conversations about the nature of scholarship within their disciplines.